Analisis Debit Banjir Pada Perencanaan Saluran Drainase Daerah Padangsambian Kelod Ruas Jalan Gunung Salak - Anak Agung Ratu Ritaka Wangsa (Jurnal Ilmiah Telsinas, 2021)
ABSTRACT: The Padangsambian Kelod area is one of the densely populated areas. This causes changes in the land use function from rice fields to housing, which reduces water infiltration, causing surface runoff. So that the author needs to calculate the flood discharge and drainage planning in the area. The stages in calculating flood discharge to planning drainage channels include looking for stations that affect, namely Ngurah Rai Station, Sanglah Station, Ship Station, conducting existing drainage channels. After that, calculate the total rainfall and maximum rainfall, which means that the data will be used for further calculations such as the consistency test of the Double Mass Analysis method, calculating the regional average rainfall, testing the selection of distribution, calculating rainfall, design the Log Person Type III method, calculating Rain intensity (Talbot, Sherman, Ishiguro), Calculating distribution suitability test (Smirnov Kolmogorov), Calculating flood discharge analysis (Rational) to dimensional calculations. In the analysis of the flood discharge, the flood discharge plan for the 5 year return period is 0.049 (m3/s)> the existing flood discharge is 0.030 (m3/s) so it is necessary to plan drainage channels in the Padangsambian Kelod area.